Dative and prepositional cases of nouns of the masculine in the Ukrainian literary language of the ХVII th century (on the basis of «Synopsis» and «Chronicle» of Ph. Sophonovich). - Фунікова, Тетяна Вікторіна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The article is based on the historical materials. This investigation is dedicated to the analysis of dative and prepositional cases of the noun system in «Synopsis» and «Chronicle» by Ph. Sophonovich, annalistic monuments of the ХVII th century, in the context of the Ukrainian literary language of the ХVII th century.In this work both archaic and new forms of nouns in chronicles which are typical for the modern Ukrainian literary language are revealed. On the basis of the investigation it is concluded that the noun system in the language of «Synopsis» and «Chronicle» by Ph. Sophonovich is a phase of transition from noun system of Old Ukrainian period to noun system of modern Ukrainian literary language. There is established that the noun system in «Synopsis», on the one hand, Keeps many archaic forms, many old inflexions and, on the other hand, includes different new forms (new inflexions, forms of plural number, etc.).